The molecular-genetic analysis of mitochondrial DNA from the burnt bones: 'the limits of the possible' problem revisited - Zemskova, E Yu; Bordyukov, M M; Kovalev, A V; Ivanov, P L (Sudebno-meditsinskaia ekspertiza, 2018)
The authors report the results of the demonstrative study continuing the cycle of interactive discussions pertinent to the possibility of obtaining reliable genetic information from the analysis of burnt bone fragments. Special emphasis is placed on the worthiness of these materials for genotyping of mitochondrial DNA (mtDNA) with the use of the standard analytical methods employed for the purpose of forensic medical expertise to investigate into the length polymorphism of the amplified mtDNA fragments (PAF) by means of sequencing with fluorescent detection. The study has demonstrated that the mtDNA fragments in the state suitable for genotyping can be found only in the preparations from the bone tissue exposed to the 'mild' thermal impact after which the affected bone is virtually indistinguishable from the native one as far as the outward appearance is concerned. In the cases of a more rigorous thermal impact when the bone tissue exhibits well pronounced signs of heat destruction, it should be considered as inherently unsuitable for genotyping of mtDNA. It was shown that chromosomal DNA is inferior to mtDNA in terms of heat resistance. This finding agrees with the currently adopted view, however this advantage of mtDNA is relatively insignificant from the standpoint of genotyping efficiency.